2019
DOI: 10.3389/fphar.2019.00988
|View full text |Cite
|
Sign up to set email alerts
|

Erxian Decoction Attenuates TNF-α Induced Osteoblast Apoptosis by Modulating the Akt/Nrf2/HO-1 Signaling Pathway

Abstract: Erxian decoction (EXD), a traditional Chinese medicine formula, has been used for treatment of osteoporosis for many years. The purpose of this study was to investigate the pharmacological effect of EXD in preventing osteoblast apoptosis and the underlying mechanism of prevention. Putative targets of EXD were predicted by network pharmacology, and functional and pathway enrichment analyses were also performed. Evaluations of bone mineral density, serum estradiol level, trabecular area fraction, serum calcium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It coincides well with the holistic ideas of 'network target, multicomponent therapeutics' of TCM and contributes greatly to the prediction of potential drugs and the screening of the components, targets as well as pathways of drugs [19]. In previous study, the network pharmacology has been used in elucidating the key components and mechanisms of TCM involved in their therapeutic effects, such as the mechanisms of Erxian Decoction against TNF-α induced osteoblast apoptosis [20], the mechanisms of Huayu-Qiangshen-Tongbi formula on rheumatoid arthritis [21], the anticancer mechanisms of Compound Kushen Injection against hepatocellular carcinoma [22].…”
Section: Introductionmentioning
confidence: 60%
“…It coincides well with the holistic ideas of 'network target, multicomponent therapeutics' of TCM and contributes greatly to the prediction of potential drugs and the screening of the components, targets as well as pathways of drugs [19]. In previous study, the network pharmacology has been used in elucidating the key components and mechanisms of TCM involved in their therapeutic effects, such as the mechanisms of Erxian Decoction against TNF-α induced osteoblast apoptosis [20], the mechanisms of Huayu-Qiangshen-Tongbi formula on rheumatoid arthritis [21], the anticancer mechanisms of Compound Kushen Injection against hepatocellular carcinoma [22].…”
Section: Introductionmentioning
confidence: 60%
“…When osteoblast precursor cells differentiate into osteoblasts, the transcription factor Runx2 is upregulated to promote the osteoblast lineage ( Vimalraj et al, 2015 ). Studies have shown that high concentration of TNF-α can induce osteoblast apoptosis ( Wang et al, 2019 ), while low concentration of TNF-α inhibits osteoblast differentiation and reduces the activity of ALP ( Bu et al, 2009 ; Yu et al, 2019 ). This effect may explain the inhibition of bone formation in chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, loss of Nrf2 increases the susceptibility of bone loss due to increased oxidative stress (Liu et al, 2019[ 43 ]; Pellegrini et al, 2017[ 46 ]; Ibáñez et al, 2014[ 26 ]); and in contrast, loss of Nrf2 accelerates bone loss, by promoting RANKL-induced osteoclast differentiation or upregulating RANKL (Hyeon et al, 2013[ 25 ]; Rana et al, 2012[ 49 ]). In addition, various natural products have been reported to have antioxidant properties through the activation of Nrf2/HO-1 signaling pathway, to protect osteoblast apoptosis caused by oxidative injury (Jin et al, 2020[ 30 ]; Wang et al, 2019[ 55 ]; Cheng et al, 2019[ 8 ]; Han et al, 2019[ 22 ], 2017[ 20 ]). Therefore, the effect of FO on the expression of Nrf2 was explored, and the results of Western blot analysis showed that the expression of p-Nrf2 protein was markedly upregulated, meaning that Nrf2 was activated in FO-treated MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%